A Quick Viability Test Protocol for Hemp (Cannabis Sativa L.) Seeds. Issue 4 (3rd April 2022) - Rachel Jacob, Sherry; Mishra, Aradhana; Kumari, Manju; Bhatt, K.C.; Gupta, Veena; Singh, Kuldeep
ABSTRACT: The viability testing in hemp seeds is a crucial step in its seed supply chain. Based on the legal status of hemp cultivation, each provincial area would benefit from the viability assessment, either by screening out dead seeds in legalized zones or by detecting the viable seeds in areas where hemp cultivation is not legalized. The routine procedure of assessing seed viability through germination tests takes a minimum of 7 days, which is practically not beneficial in the seed supply system. There is a need for developing a quick, reproducible, and fool-proof technique whereby seed lots can be rapidly screened, utilizing minimum resources. In this experiment, we have standardized a tetrazolium-based viability testing protocol which can identify the viability status of seed lots within 3 h.